1996
DOI: 10.1002/(sici)1098-2302(199604)29:3<191::aid-dev1>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Stress reactivity and attachment security

Abstract: Seventy-three 18-month-olds were tested in the Ainsworth Strange Situation. These children were a subset of 83 infants tested at 2, 4, 6, and 15 months during their well-baby examinations with inoculations. Salivary cortisol, behavioral distress, and maternal responsiveness measures obtained during these clinic visits were examined in relation to attachment classifications. In addition, parental report measures of the children's social fearfulness in the 2nd year of life were used to classify the children into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 0 publications
2
38
0
1
Order By: Relevance
“…A partial survey of findings to date demonstrates its relevance to stress response [9,14,15]; relationship with care providers in diabetic patients [10,70]; pain [12,32,94]; chronic diseases, including ulcerative colitis [9]; alopecia, leg ulcers, and breast cancer [13,95]; somatization [11,96]; hypochondriacal concerns [31]; and health care utilization [72]. In psychosomatic research, the most commonly used scales to date are the AAI, the ECR-R, the RQ, the AAS, and the ASQ.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A partial survey of findings to date demonstrates its relevance to stress response [9,14,15]; relationship with care providers in diabetic patients [10,70]; pain [12,32,94]; chronic diseases, including ulcerative colitis [9]; alopecia, leg ulcers, and breast cancer [13,95]; somatization [11,96]; hypochondriacal concerns [31]; and health care utilization [72]. In psychosomatic research, the most commonly used scales to date are the AAI, the ECR-R, the RQ, the AAS, and the ASQ.…”
Section: Discussionmentioning
confidence: 99%
“…The ambivalent/resistant infant also shows distress on separation, but signals for and resists contact upon the caregiver's return. The avoidant infant may or may not manifest behavioral signs of distress upon separation from the caregiver, although physiological indices suggest high reactivity [15,16]. The infant essentially ignores the caregiver on re-union and shows little outward indication of distress.…”
Section: Measurement Of Attachment: Ainsworth Et Al's Strange Situatmentioning
confidence: 99%
See 1 more Smart Citation
“…Among first-graders in the United States, DeCaro and Worthman (2008) show that greater instability in the maternal-child relationship is associated with higher evening cortisol levels. Research on attachment and cortisol finds that infants and toddlers classified as highly fearful and insecure or as having disorganized/disoriented attachment have higher cortisol levels than those children classified as securely attached (Gunnar et al 1996;Hertsgaard et al 1995). Further evidence suggests that parental mood can be internalized by children into a stress response: a study of children aged 6-10 years from low, middle, and high socioeconomic backgrounds found that children from the low SES group had the highest salivary cortisol profiles and that cortisol values were correlated with mother's score on a depression scale (Lupien et al 2000).…”
Section: The Neuroendocrine Stress Response As a Biological Mechanismmentioning
confidence: 99%
“…This gave rise to a number of studies on the role of cortisol in attachment. Several studies have shown cortisol reactivity in 1-yearolds to be related to attachment security (Gunnar, Brodersen, Nachmias, Buss, & Rigatuso, 1996;Hertsgaard, Gunnar, Erickson, & Nachmias, 1995;Nachmias, Gunnar, Mangelsdorf, Parritz, & Buss, 1996;Spangler & Schieche, 1998). The adrenocortical system appears to react most strongly in potentially threatening situations, when the resources to cope with the threat are lacking (Kirschbaum & Hellhammer, 1994;McEwen & Sapolsky, 1995;Nachmias et al, 1996;Spangler & Scheubeck, 1993).…”
Section: Introductionmentioning
confidence: 99%